Resepsi Thibbun Nabawi pada Hastag #JurusSehatRasulullah (JSR) Ala Zaidul Akbar - Sari, Maula; Zuhri, Syaifuddin (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2021)
Thibbun Nabawi is a transformation between past and present due to viralization.  Thibbun Nabawi has been known since the time of the Prophet, along with his journey Nabawi experienced changes in marketing and introduction. One of the viral phenomena especially in social media now is #JSR or JurusSehatRasulullah which was pioneered by Zaidul Akbar with a more dynamic nuance, and easily practiced by the wider community. This paper aims to look at the reception of the Koran in the online world, especially JurusSehatRasulullah (#JSR) by Zaidul Akbar, and the #JSR's response and impact to netizens. This research is qualitative by using reception theory and discourse analysis. The results of this study indicate that the JSR in the style of  Zaidul Akbar provides positive results for netizens who practice it. The number of positive testimonials given by netizens. The hashtag #JSR makes it easy for people to access health knowledge taught by the Koran and its sunnah.